Tests Construction, Validation, Evaluation and Documentation: The Hallmark of Tests and Measurement (2019)
The heart of a teacher's test is the items. Many kinds of items can be used effectively in classroom tests and there are principles or “tricks of the trade” that can help teachers to develop good test items. We shall examine the most generally useful of these principles after first considering differences among the several kinds of items used in classroom tests. A standardize test is a type of test that is constructed using systematic procedure that ensures objectivity and uniformity in its construction, validation, scoring and interpretation. Test generally is a stimulus that is used to elicit response from the testees. There are different types of test, it ranges from typical response test which consist of any test that measure any psychological construct ranging from interest, attitude, personality, intelligence and maximum performance test which consists of mental ability test, achievement test and aptitude test. In itemizing the procedure to be followed in constructing standardized test however, the procedure for both typical response test, that is either psychological test or performance test is outlined below.